Music and Manipulation: On the Social Uses and Social Control of Music - Brown, Steven; Volgsten, Ulrik (New York, NY Berghahn Books, 2006)
Since the beginning of human civilization, music has been used as a device to control social behavior, where it has operated as much to promote solidarity within groups as hostility between competing groups. Music is an emotive manipulator that influences attitude, motivation and behavior at many levels and in many contexts. This volume is the first to address the social ramifications of music's behaviorally manipulative effects, its morally questionable uses and control mechanisms, and its economic and artistic regulation through commercialization, thus highlighting not only music's diverse uses at the social level but also the ever-fragile relationship between aesthetics and morality.
Keywords: Music; Politics; Sociology